Kebijakan Reformulasi Tindak Pidana Penipuan Dalam Transaksi Elektronik (Reformulation Policy Of Fraud In Electronic Transactions) - Rumlus, Muhamad Hasan (Program Studi Hukum Universitas Pendidikan Muhammadiyah Sorong, 2022)
In this article, we will answer the reformulation of the article on fraud in the ITE Law which is firm and comprehensive in tackling the crime of fraud in electronic transactions. This problem arises from the lack of clarity in the current regulations regarding security in conducting electronic transactions and protection against criminal acts of fraud in electronic transactions. Methods This research uses a normative juridical approach to legislation and a case approach. There are 3 (three) obscuration of norms as a result of the use of Article 28 paragraph (1) of the ITE Law, namely First, Article 28 paragraph (1) of the ITE Law when used is only able to ensnare some actors, namely only limited to consumers and producers, second, Article 28 paragraph (1) The ITE Law is still not comprehensive enough to be used by law enforcement in criminal acts of fraud in electronic transactions, while Article 28 (1) of the ITE Law related to the phrase